LEARNING FOREIGN LANGUAGES FOR FUN: Yangi O'zbekiston taraqqiyotida tadqiqotlar o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Gamification is the application of game elements and principles in non-game contexts to enhance engagement, motivation, and learning. In the context of language education, gamification has been increasingly utilized to make the language learning process more enjoyable and effective.